Uang Fiat Dan Operasi Pasar Terbuka: Tinjauan Ekonomi Islam - Hardi, Eja Armaz (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
This article aims to discuss monetary policy in Indonesia, namely Open Market Operations (OPT) on Islamic economics perspective. OPT known as the monetary instrument, which most often used to achieve policy objectives. In general, monetary targets aimed to stimulate the economic growth and inflation stabilization. OPT’s policy products included Bank Indonesia Certificates (SBI), Sharia Bank Indonesia Certificates (SBIS), Bank Indonesia Wadiah Certificates (SWBI), Government Securities (SUN), Sukuk, Private Bonds, Rupiah Interventions (IR), and Loan Facilities Bank Indonesia (FASBI) which is traded on the money market; the primary market and the secondary market with an auction system. Currently, All OPT products based on fiat money. The buy and sell system of OPT products uses a discount system and interest rates. Money plays an important role in the economy, so the policy of monetary contraction and expansion of the amount of money circulating in society will affect the velocity of money. With a descriptive analysis, this article analyzes the role of fiat money from the perspective of Islamic economics. This article argues that the three schools of thought in Islamic economics agree that the function of money used as a means of transaction, investment, and precaution. As an exchange style, money unable to be used as a means of future speculation. Thus, the Islamic economy views that underlying of Islamic monetary policy based on the productivity of the real sector and oriented to the welfare of society.